2016
DOI: 10.1016/j.smim.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of memory T cell subsets for adoptive immunotherapy

Abstract: Adoptive transfer of primary (unmodified) or genetically engineered antigen-specific T cells has demonstrated astonishing clinical results in the treatment of infections and some malignancies. Besides the definition of optimal targets and antigen receptors, the differentiation status of transferred T cells is emerging as a crucial parameter for generating cell products with optimal efficacy and safety profiles. Long-living memory T cells subdivide into phenotypically as well as functionally different subsets (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
191
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(198 citation statements)
references
References 76 publications
6
191
0
1
Order By: Relevance
“…1-3,5-9,25,29,32,34 This perspective should promote further research and clinical translation of adoptive T cell therapy with interference of the PI3K/AKT/mTOR or Wnt-signalling pathway. 15-19,21,33 Here we show that AKT-inhibition can be used for the generation of a unique T SCM -like CD8 + T cell product for adoptive transfer.…”
Section: Discussionmentioning
confidence: 99%
“…1-3,5-9,25,29,32,34 This perspective should promote further research and clinical translation of adoptive T cell therapy with interference of the PI3K/AKT/mTOR or Wnt-signalling pathway. 15-19,21,33 Here we show that AKT-inhibition can be used for the generation of a unique T SCM -like CD8 + T cell product for adoptive transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetically, T cells silence stemness genes during the acquisition of effector gene expression (Buchholz et al, 2013; Crompton et al, 2016; Henning et al, 2018a, 2018b; Restifo and Gattinoni, 2013). Unlike effector T cells, minimally differentiated naive and memory T cells are stem cell-like and capable of robust expansion, immune reconstitution, and long-term persistence, qualities that make them of great clinical interest (Busch et al, 2016). In fact, it has been shown that such minimally differentiated T cells possess superior anti-tumor properties upon adoptive transfer in vivo and are associated with longer persistence (Gattinoni et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…8,9,19,28 Drawbacks of ex vivo techniques include high cost and lack of a memory T-cell population after inoculation into the patient. 29,30 Nanoparticle delivery systems have had some success, but often they are targeted only to macrophages and dendritic cells, and most targeted systems require costly antibodies or peptides that are difficult to store and scale up to pharmaceutical quantities. 8,9 The advantage of using OPSS-liposomes is that OPSS is a small low-cost molecule that binds endogenous complement C3 and targets all three APCs, including B cells.…”
mentioning
confidence: 99%